Integrating Analytical Techniques with Business Strategic Decision-Making - Kučinskienė, Marija; Jatuliavičienė, Gražina (Ekonomika, 2004)
The paper offers a discussion about the impact of strategic position on strategic decision-making. Many transitional countries are solving the problem of criteria, their selection and evaluation for a successful competition in the global environment. The theoretical aspects of the application of analytical techniques in strategic decision-making and the ways how strategic decisions, based on these techniques, should be made by Lithuanian dairy product producers are discussed. The analysis shows that adaptability is the essential characteristic of decision making for the future of an enterprise, and up-ta-date techniques should be included into strategic thinking.